IMPLEMENTASI SISTEM PEMANTAUAN DAN AKUISISI DATA SENSOR PADA TANGKI SEPARATOR MENGGUNAKAN HMI CIMON CM-EXT07-D - -, Supra; Sugiharto, Jarot (UPPM Politeknik TEDC Bandung, 2025)
In the industry, a good control system is required to support the production process and optimize efficiency in production. A monitoring system is a system used to oversee the work process within a plant design. Such systems are widely used and applied in the industrial world to assess the performance of a plant. This monitoring system can be implemented locally or remotely. In close-range monitoring systems, indicators are typically displayed on meters located on a panel near the Automatic Transfer Switch – Main Failure (ATS – MF) equipment. Meanwhile, for remote monitoring, the internet is often utilized, commonly referred to as the Internet of Things (IoT). The monitoring system in question is the monitoring system on a separator. Inaccuracies in monitoring, such as pressure, system separation, and others, significantly affect the performance of the separator system. Without a monitoring system, the performance of the separator, especially in separating steam from water, is inaccurate and time-consuming due to manual monitoring. Therefore, a monitoring system is needed to improve the performance of the separator, which can be achieved by using an HMI (Human Machine Interface). Using HMI allows for monitoring the separation process within the separator tank, improving system performance and saving time. This facilitates the monitoring process. This can facilitate the monitoring stage that is conducted. With this monitoring system, it becomes easier to observe or monitor the required pressure and temperature produced by the device.